Language Rights as Collective Rights: Some Conceptual Considerations on Language Rights - Toscano Méndez, Manuel (Res Publica. Revista de Historia de las Ideas Políticas, 2015)
Stephen May holds that language rights have been insufficiently recognized, or just rejected as problematic, in human rights theory and practice. Defending the “human rights approach to language rights”, he claims that language rights should be accorded the status of fundamental human rights, recognized as such by states and international organizations. This article argues that the notion of language rights is far from clear. According to May, one key reason for rejecting the claim that language rights should be considered human rights is the widespread belief that language rights are collective rights. In order to address this kind of objection, the collective character attributed to language rights must be carefully assessed, distinguishing two different views of what a collective right is.